Healthy excursions outside the thermal comfort zone. Issue 7 (3rd October 2017) - van Marken Lichtenbelt, Wouter; Hanssen, Mark; Pallubinsky, Hannah; Kingma, Boris; Schellen, Lisje
ABSTRACT: The concepts of comfort and health may be related but are not synonyms. New knowledge has been gathered regarding metabolic health effects of temperature exposure outside the human thermal comfort zone. Mild cold and warm environments increase metabolism, thereby targeting obesity by counterbalancing excess energy intake. Furthermore, mild cold influences glucose metabolism. Ten days of intermittent mild cold exposure in type 2 diabetes patients increased insulin sensitivity, and thereby glucose handling by more than 40%. This is comparable with the best available pharmaceutical or physical activity therapies. Lastly, there are indications that cardiovascular parameters may be positively affected by regular exposure to heat and cold. Does this mean that we have to suffer from discomfort in order to become healthy? Probably not. Firstly, prolonged temporal excursions outside the thermal comfort zone result in acclimatization resulting in increased comfort ratings. Secondly, low or high temperatures in a dynamic thermal environment may be perceived as acceptable or even pleasant (evoking thermal alliesthesia). The study of dynamic thermal conditions is advocated: linking this to the adaptive comfort model, and monitoring these conditions in actual living conditions. This information is needed to support the design of healthy, comfortable and energy-friendly indoor environments.